A Preaching Communication Approach to Instilling the Values of Religious Moderation at the Al-Mubarok Pajo Islamic Boarding School - Firmansyah Firmansyah; St. Fatimah Azzahra (STKIP Taman Siswa Bima, 2025)
The approach of da'wah communication in instilling the values of religious moderation aims to form a tolerant, balanced, and peaceful understanding of religion, and avoid extreme attitudes (radical or liberal). In this context, the da'wah approach needs to be adjusted so that the message about wasathiyah (moderation) in Islam can be accepted and internalized. This study aims to identify the values of religious moderation in the Al-Mubarok Pajo Islamic boarding school, and aims to determine how the da'wah communication approach in instills the values of religious moderation in the Al-Mubarok Pajo Islamic boarding school. This type of research uses a field research with a qualitative approach. Qualitative descriptive data analysis with the Miles and Huberman data analysis model which includes three main stages, namely: Data Reduction, Data Presentation and Conclusion Drawing. The results of this study indicate that the values of religious moderation at the Al-Mubarok Pajo Islamic boarding school include Tawassut (middle way), I'tidal (Justice and Proportional), Tasamuh (tolerance), Asy-Shura (deliberation), Al-Muwathanah (love of the homeland), Al-La'unf (anti-violence) and I'tiraf Al-'urf (friendly culture). Using da'wah media through education, and internet media. The da'wah communication approach in instilling the values of religious moderation at the Al-Mubarok Pajo Islamic boarding school is using Da'wah bil-lisan, bil-qalam, and bil-hal with a persuasive, educational, and dialogical approach. The interpersonal approach is humanistic and contextual, adapted to the social and cultural conditions of the community. And the da'wah carried out is not judgmental, but encourages an inclusive and peaceful religious understanding.